Wetting Bahaviour and Reactivity between Liquid Gd and ZrO2 Substrate - Turalska, Patrycja; Homa, Marta; Bruzda, Grzegorz; Sobczak, Natalia; Kaban, Ivan; Mattern, Norbert; Eckert, Jürgen (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Wetting behavior and reactivity between molten pure Gd and polycrystalline 3YSZ substrate (ZrO2 stabilized with 3 wt% of Y2O3) was experimentally determined by a sessile drop method using classical contact heating procedure coupled with drop pushing procedure. The test was performed under an inert flowing gas atmosphere (Ar) at two temperatures of 1362 °C and 1412 °C. Immediately after melting (Tm=1341°C), liquid Gd did not wet the substrate forming the contact angle of θ=141°. The non-wetting to wetting transition (θ < 90°) took place after about 110 seconds of interaction and was accompanied by a sudden decrease in the contact angle value from θ=141° to θ=67°. Further heating of the Gd/3YSZ couple to test temperature did not affect its value and the final contact angle value after wettability test was established as θf=67°±1°. The solidified Gd/3YSZ sessile drop couple was studied by means of optical microscopy and scanning electron microscopy coupled with X-ray energy diffraction spectroscopy. Structural investigations revealed that the wettability in the Gd/3YSZ system is of a reactive nature and it is associated with the formation of a continuous layer of a wettable reaction product Gd2Zr2O7.